2009
DOI: 10.1093/molbev/msp289
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Population-Based and Deep Sequencing Data to Identify Coevolving Sites in the nef Gene of HIV-1

Abstract: Rapidly evolving viruses such as HIV-1 display extensive sequence variation in response to host-specific selection, while simultaneously maintaining functions that are critical to replication and infectivity. This apparent conflict between diversifying and purifying selection may be resolved by an abundance of epistatic interactions such that the same functional requirements can be met by highly divergent sequences. We investigate this hypothesis by conducting an extensive characterization of sequence variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 64 publications
0
55
0
Order By: Relevance
“…It is difficult to determine whether these inconsistencies are the result of technical errors or simply the failure to amplify, sequence, and detect consistently low-frequency variants. Variability between replicated UDS runs on the 454 platform has previously been reported (61,68). For example, Poon et al (61) found that many minority variants detected at levels between 1 and 5% in one replicate were undetectable in another.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is difficult to determine whether these inconsistencies are the result of technical errors or simply the failure to amplify, sequence, and detect consistently low-frequency variants. Variability between replicated UDS runs on the 454 platform has previously been reported (61,68). For example, Poon et al (61) found that many minority variants detected at levels between 1 and 5% in one replicate were undetectable in another.…”
Section: Discussionmentioning
confidence: 93%
“…Variability between replicated UDS runs on the 454 platform has previously been reported (61,68). For example, Poon et al (61) found that many minority variants detected at levels between 1 and 5% in one replicate were undetectable in another. Therefore, we believe that our filtering and background-calling procedure is unlikely to be the sole source of incongruent results between duplicate UDS runs and that other sources of noise could play a role, including PCR and sampling biases and various UDS instrument errors.…”
Section: Discussionmentioning
confidence: 93%
“…Here, we made a number of simplifications. (i) Epistasis is known to exist for other RNA viruses (45)(46)(47)(48) and has been reported for HIV (49,50); it may contribute to the average values of LD. We hope that the importance of epistasis for the HIV genome in vivo will become clearer in the future, but we have ignored it here.…”
Section: Discussionmentioning
confidence: 96%
“…Sites V74, A83, and D175 lie within motifs implicated in the modulation of cell signaling pathways by Nef (20). While site S169 has no previously identified role in Nef function, a recent analysis showed that this site is coevolving with N157 and is therefore likely to have some functional role (51). The remaining six other sites under purifying selection (N52, A84, Y135, G140, H171, and V180) have no previously defined associations with known functions of Nef.…”
Section: Figmentioning
confidence: 99%